Transarterial radioembolization versus chemoembolization for hepatocellular carcinoma: a meta-analysis - Lu, Wenxiao; Zhang, Tongsheng; Xia, Fengfei; Huang, Xiangzhong; Gao, Fulei (Frontiers in Oncology, 2025)
BackgroundCurrently, inoperable hepatocellular carcinoma (HCC) is treated by both transarterial radioembolization (TARE) and transarterial chemoembolization (TACE). However, their relative efficacy and outcomes remain unclear. This meta-analysis aimed to compare TARE and TACE to evaluate their safety and efficacy in treating inoperable HCC patients.MethodsRelevant studies were identified by searching the Web of Science, PubMed, and Wanfang databases. Pooled analyses were used to compare treatment response rates, complications, and overall survival (OS) outcomes between the TARE and TACE groups.ResultsThis analysis selected 8 studies comprising 1026 and 358 patients that respectively underwent TACE and TARE treatment. The results revealed that the TARE group had significantly higher pooled total response, disease control, and 1-year OS rates compared to the TACE group (P = 0.04, 0.003, and 0.02, respectively), with a corresponding increase in OS (P = 0.0002). Furthermore, rates of complications including fever and abdominal pain were also reduced in the TARE group (P = 0.006 and 0.02, respectively). Moreover, there were no significant differences in the pooled analyses of complete response rates, fatigue, nausea/vomiting, 3-year OS, or 5-year OS between these groups (P = 0.24, 0.69, 0.15, 0.73, and 0.38, respectively). Significant heterogeneity was detected for endpoints including fatigue, nausea/vomiting, fever, abdominal pain, OS duration, and 3-year OS (I2 = 89%, 82%, 72%, 90%, 96%, and 66%, respectively). All endpoints exhibited no significant risk of publication bias.ConclusionsThis study revealed that relative to TACE, TARE performed using 90Y can yield significantly higher treatment response rates and prolong HCC patient survival with fewer treatment-related side effects.The PRISMA guidelines were used to guide the execution and publication of this meta-analysis. The study is registered at INPLASY.COM (No. INPLASY202380017).Systematic review registrationINPLASY.COM, identifier INPLASY202380017.